Proposta de regionalização para constituição de consórcios públicos para gestão integrada de resíduos sólidos urbano - Gomes, Aline Pimentel (2021)
The constitution of public consortia is an alternative for the joint resolution of Urban Solid Waste (MSW) management problems. Public consortia provide the execution of public services and policies with greater efficiency, agility and transparency, as well as rationalize and optimize the use of public resources. In this way, regionalization studies are important to enable the creation of public consortia, since they provide a database capable of facilitating the understanding or negotiations among different municipal managers, streamlining the process of constituting consortia. This research aims to contribute to the elaboration of regionalization studies and to the establishment of inter-municipal public consortia for MSW management. Through structured questionnaires, technical visits, observations and photographic records, consultations on consortium websites and document analysis, public consortia for the MSW management in the country were identified and mapped, inter-municipal cooperations for MSW management in Brazil and in Europe were researched, regionalization studies for MSW management in Brazilian states were analyzed, guidelines for the preparation and implementation of regionalization plans were proposed and guidelines for identifying territorial arrangements of municipalities for the establishment of public consortia in the state of Rio Grande do Sul were applied. As results, 258 public consortia were identified, located mainly in the Southeast, Northeast and South regions, the majority formed by municipalities of up to 50 thousand inhabitants. The consortia visited in Brazil and Europe, despite political, technical, managerial and financial obstacles, prove the benefits of regionalized management. The regionalization plans of the Brazilian states indicated a great difference regarding the number of proposed regions, the number of participating municipalities, the area and the population in each region, the technical criteria used, the hierarchy of these criteria and the methods and tools that helped the elaboration process. The definition of guidelines for the elaboration, maintenance and monitoring of regionalization studies and guidelines for the definition of territorial arrangements between municipalities contribute to the formation of public consortia. As conclusions, it is highlighted that the results reported in this study may support the elaboration of regionalization studies and public policies in the area of MSW management and regional planning, in addition to provoking the debate about the formation of public consortia.